PLD1 is a key player in cancer stemness and chemoresistance: Therapeutic targeting of cross-talk between the PI3K/Akt and Wnt/β-catenin pathways - Seong Hun Lim; Hyesung Lee; Hyun Ji Lee; Kuglae Kim; Junjeong Choi; Jung Min Han; Do Sik Min (Experimental and Molecular Medicine)
Abstract The development of chemoresistance is a major challenge in the treatment of several types of cancers in clinical settings. Stemness and chemoresistance are the chief causes of poor clinical outcomes. In this context, we hypothesized that understanding the signaling pathways responsible for chemoresistance in cancers is crucial for the development of novel targeted therapies to overcome drug resistance. Among the aberrantly activated pathways, the PI3K-Akt/Wnt/β-catenin signaling pathway is clinically implicated in malignancies such as colorectal cancer (CRC) and glioblastoma multiforme (GBM). Aberrant dysregulation of phospholipase D (PLD) has been implicated in several malignancies, and oncogenic activation of this pathway facilitates tumor proliferation, stemness, and chemoresistance. Crosstalk involving the PLD and Wnt/β-catenin pathways promotes the progression of CRC and GBM and reduces the sensitivity of cancer cells to standard therapies. Notably, both pathways are tightly regulated and connected at multiple levels by upstream and downstream effectors. Thus, gaining deeper insights into the interactions between these pathways would help researchers discover unique therapeutic targets for the management of drug-resistant cancers. Here, we review the molecular mechanisms by which PLD signaling stimulates stemness and chemoresistance in CRC and GBM. Thus, the current review aims to address the importance of PLD as a central player coordinating cross-talk between the PI3K/Akt and Wnt/β-catenin pathways and proposes the possibility of targeting these pathways to improve cancer therapy and overcome drug resistance.